2007
DOI: 10.1007/s00253-006-0657-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron donors and acceptors on anaerobic reduction of azo dyes by Shewanella decolorationis S12

Abstract: Shewanella decolorationis S12 was able to reduce various azo dyes in a defined medium with formate, lactate, and pyruvate or H(2) as electron donors under anaerobic conditions. Purified membranous, periplasmic, and cytoplasmic fractions from strain S12 analyzed, respectively, only membranous fraction was capable of reducing azo dye in the presence of electron donor, indicating that the enzyme system for anaerobic azoreduction was located on cellular membrane. Respiratory inhibitor Cu(2+), dicumarol, stigmatell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Then, another experiment was designed with the usage of purified membranous, periplasmic, and cytoplasmic fractions from S. decolorationis S12 to decolorize azo dyes (Hong et al 2007b). They realised that only the membranous fraction was capable of reducing azo dye in the presence of an electron donor, indicating that the enzyme system for anaerobic azoreduction was located on cellular membrane.…”
Section: Biochemical Mechanisms Of Azo Dye Degradation By Shewanella mentioning
confidence: 99%
“…Then, another experiment was designed with the usage of purified membranous, periplasmic, and cytoplasmic fractions from S. decolorationis S12 to decolorize azo dyes (Hong et al 2007b). They realised that only the membranous fraction was capable of reducing azo dye in the presence of an electron donor, indicating that the enzyme system for anaerobic azoreduction was located on cellular membrane.…”
Section: Biochemical Mechanisms Of Azo Dye Degradation By Shewanella mentioning
confidence: 99%
“…Most of the anaerobic reduction processes are location specific but can take place both in cytoplasmic and membrane fractions isolated from bacterial cells (Kudlich et al, 1997). However, an essential component required for electron transport from electron donors to azo compounds is thought to be located in membrane fractions from bacterial cell extracts (Hong et al, 2007a(Hong et al, , 2009). This implies that the coupling of oxidation of electron donor and reduction of azo dyes is a universal biochemical phenomenon for azo dyes degradation.…”
Section: Sphingomonas Paucimobilismentioning
confidence: 99%
“…Likewise, Elbanna et al (2010) reported a complete mineralization of Reactive Lanasol Black B (RLB), Eriochrome Red B (RN) and 1,2 Metal Complexes I Yellow in anaerobic-aerobic sequential system using a consortium of Lactobacillus casei, Lactobacillus paracasei and Lactobacillus rhamnosus. Single strains can also perform the sequential process, but may be less efficient, leading to partial degradation of azo dyes (Hong et al, 2007a). In one such study, Hong et al (2007a) used the bacterial strain Shewanella decolorationis S12, which completely decolorized the Amaranth dye under anaerobic conditions, but when it was exposed to aerobic conditions, the byproducts of amaranth (1-aminenaphthylene-4-sulfonic acid and 1-aminenaphthylene-2-hydroxy-3,6-disulfonic acid) were only partially mineralized.…”
Section: Biodegradation Via Sequential Reduction-oxidation Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of dye decolorization by the aid of redox mediators has also been reported by other researchers. Hong et al (2007c) revealed that the DE (%) of 1.0 mmol l À1 amaranth degraded by S. decolorationis S12 (20.0 mmol l À1 formate as electron donor) was increased by about 21% with the addition of 5.0 mmol l À1 or 10.0 mmol l À1 Fe(III)-citrate. Hong et al (2007b) also reported that low concentration of anthraquinone-2-sulfonate (AQS) (about 1.0e3.0 mmol l À1 ) accelerated the decolorization of azo dye by strain S12.…”
mentioning
confidence: 99%